The evolution of the human capital of women - Audra J. Bowlus; Chris Robinson (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
The labor market attachment of females has increased dramatically over the last half century, converging to a pattern similar to that of males. Human capital theory predicts an associated increase in human capital investment by females and a convergence in the life-cycle human capital investment profiles of males and females. This paper explores wage-based and job-skills-based approaches to measuring the increased supply of efficiency units of human capital by females over the last four decades. Results suggest that the magnitude of the contribution of the in-creased human capital of women to post-war economic growth is substantially under-estimated by conventional methods of measuring human capital and labor inputs. A complete picture of the evolution of the human capital of women requires new approaches to measuring their human capital.
Keywords: 330